Alleviation of Salinity Stress in Peanut by Application of Endophytic Bacteria - Pal, Kamal K.; Dey, Rinku; Sherathia, Dharmesh N.; Devidayal,; Mangalassery, Shamsudheen; Kumar, Arvind; Rupapara, Rupal B.; Mandaliya, Mona; Rawal, Priya; Bhadania, Roshani A.; Thomas, Manesh; Patel, Mili B.; et al. (Frontiers in Microbiology, 2021)
Development of salinity, which affects 7% of world’s land surface, is a major constraint to crop productivity. We attempted use of co-evolving endophytes of peanut to alleviate salinity stress and enhance yield of peanut. Diverse and different tissue colonizing endophytes were isolated from peanut and screened in vitro by seed germination bioassay imposing gradients of salinity, with two cultivars TG37A (susceptible) and GG2 (moderately resistant), and in potted conditions using saline irrigation water. Finally, nine endophytes capable of producing IAA and ACC-deaminase, promoting root growth and yield in potted conditions were selected for further evaluation in field condition. They were evaluated with saline water (1.5-2.0 dS/m) in saline soil with susceptible cultivar TG37A. Simultaneously, three endophytes (Bacillus firmus J22N; Bacillus tequilensis SEN15N: and Bacillus sp. REN51N) were evaluated with two cultivars, GG2 and TG37A, during rainy and post-rainy seasons with elevated salinity. Application of endophytes like Bacillus firmus J22N and Bacillus sp. REN51N enhanced pod and haulm yield of peanut by 14-19% across cultivars, salinity and seasons. In addition, there was significant modulation in parameters like relative water content; production of enzymes like superoxide dismutase (SOD), glutathione reductase (GR), catalase (CAT), ascorbate peroxidase (APX), lipid peroxidase (POD), and H2O2 content in leaf; and uptake of potassium. Activities of enzymes involved in scavenging of reactive oxygen species (ROS) increased with salinity, and further increased with endophytes like Bacillus firmus J22N, Bacillus tequilensis SEN15N and Bacillus sp. REN51N. Besides, there was enhanced accumulation of proline, reduced level of phenol and H2O2 and enhanced uptake of potassium with the inoculation of endophytes. Improving the scavenging capacity of plants by endophytic modulation of ROS scavengers, uptake of K, production of ACC deaminase and IAA, root and biomass growth, modulation in relative water content and enhanced accumulation of osmoprotectant might be the reasons of alleviation of salinity stress by endophytes in peanut by endophytes. This is the first time that mechanism of alleviation of salinity stress in peanut has been unraveled at field level and their potential demonstrated. Application of these endophytes will bring agricultural sustainability in salinity-affected areas in future, as an ameliorating measure.